Density-Diffusion Relationship in Soda-Lime Phosphosilicate - Ouldhnini, Youssef; Atila, Achraf; Ouaskit, Said; Hasnaoui, Abdellatif (Journal of Non-Crystalline Solids, 2022)
Bioactive glasses release ions such as sodium when implanted in the human body. However, an excess of the released ions can cause problems related to cytotoxicity. The ion release control is considered one of the primary challenges in developing new bioactive glasses. Here, we use molecular dynamics simulations to investigate the effect of the density on atoms’ dynamics in an archetypal phosphosilicate bioactive system. The diffusion coefficient displays three main regimes with increasing density. The mobility of the modifiers is significantly affected by the increase of the density, especially Na, compared to other elements. We use a modified Arrhenian model to access the complex dynamic behavior of 45S5 melts and correlate it to the structural changes by evaluating the network connectivity and pair-excess entropy. Overall, our results present a step toward the rational design of bioactive glasses and a key to controlling the ion release of bioactive glasses.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Bioactive glasses; Diffusion; Molecular dynamics; Structural properties